Effect of free nitrous acid pre-treatment on primary sludge at low exposure times. (March 2017) - Zahedi, S.; Icaran, P.; Yuan, Z.; Pijuan, M.
Highlights: pH control is not necessary during FNA pre-treatment on primary sludge (PS). FNA increases the solubility and reduces cell viability (<20%). At 1 h, FNA (with 650 mg N-NO2 − ) provided the highest methane production (MP). Similar enhancement on MP were obtained while subjecting the PS at mild at 2–5 h. FNA is not necessary to increase MP; mild agitations also improve MP (around 14–17%). Abstract: The present study was undertaken to investigate the effect of different free nitrous acid (FNA) concentrations at low pre-treatment times (PTs) (1, 2 and 5 h) and without pH control with mild agitation on primary sludge (PS) biodegradability and methane production (MP). Increasing PTs resulted in an increase in the solubility of the organic matter (around 25%), but not on cell-mortality (>75% in all the cases with FNA) and neither on methane generation. FNA pre-treatment at low PTs improve MP (around 16% at PT of 1 h and 650 mg N-NO2 − /L). However, a similar improvement was found with mild agitation of PS without FNA at 2 and 5 h. Taking into account the potential costs associated with the FNA pre-treatment, a mild agitation without FNA would be preferred to enhance MP in PS.